PENGALAMAN POSITIF INTERAKSI KOMUNITAS GAME ONLINE DAN ARTI PENTINGNYA DALAM MENINGKATKAN KOMPETENSI SOSIAL OFFLINE PADA REMAJA - Helmi Bayuputra, Rafli; Surayya Ulfa, Nurist; Setyabudi, Djoko (Interaksi Online, 2024)
Online games are an important part of the lives of Indonesian teenagers today. This research also shows that online games have a positive effect also in the aspect of friendship, this cannot be separated from the sharpening of social interactions so that they can provide important meaning to teenagers' social competence. This research uses the Miles and Huberman model. The results of the research show that the social skills model, appreciation/giving rewards, social intelligence and problem solving, assertiveness, non-verbal and verbal communication and personal perception are included in the Interaction-Process Analysis theory by Robert Bales in Little John (1983), namely social interaction and individual roles. In this theory of social interaction, it emphasizes how important it is to understand the dynamics of social interaction. Meanwhile, the Personal Perception aspect was included in Robert Bales in Little John (1983), namely individual interaction. This theory highlights the role of individuals in social interactions. In the context of research, researchers can explore the roles played by online game players in their games and how these roles can influence their interactions outside the game or in their real lives as teenagers